A Novel Bromodomain Inhibitor Reverses HIV-1 Latency through Specific Binding with BRD4 to Promote Tat and P-TEFb Association - Huang, Huachao; Liu, Shuai; Jean, Maxime; Simpson, Sydney; Huang, He; Merkley, Mark; Hayashi, Tsuyoshi; Kong, Weili; Rodríguez-Sánchez, Irene; Zhang, Xiaofeng; Yosief, Hailemichael O.; Miao, Hongyu; et al. (Frontiers in Microbiology, 2017)
While combinatory antiretroviral therapy (cART) can effectively reduce HIV-1 viremia, it cannot eliminate HIV-1 infection. In the presence of cART, viral reservoirs remain latent, impeding the cure of HIV-1/AIDS. Recently, latency-reversing agents (LRAs) have been developed with the intent of purging latent HIV-1, providing an intriguing strategy for the eradication of the residual viral reservoirs. Our earlier studies show that the first-generation, methyl-triazolo bromodomain, and extra-terminal domain inhibitor (BETi), JQ1, facilitates the reversal of HIV-1 latency. BETis have emerged as a new class of compounds that are promising for this HIV-1 “shock and kill” eradication approach. However, when used as a single drug, JQ1 only modestly reverses HIV-1 latency, which complicates studying the underlining mechanisms. Meanwhile, it has been widely discussed that the induction of latent proviruses is stochastic (Ho et al., 2013). Thus, new BETis are currently under active development with focus on improving potency, ease of synthesis and structural diversity. Using fluorous-tagged multicomponent reactions, we developed a novel second-generation, 3,5-dimethylisoxazole BETi based on an imidazo[1,2-a] pyrazine scaffold, UMB-32. Furthermore, we screened 37 UMB-32 derivatives and identified that one, UMB-136, reactivates HIV-1 in multiple cell models of HIV-1 latency with better efficiency than either JQ1 or UMB-32. UMB-136 enhances HIV-1 transcription and increases viral production through the release of P-TEFb. Importantly, UMB-136 enhances the latency-reversing effects of PKC agonists (prostratin, bryostatin-1) in CD8-depleted PBMCs containing latent viral reservoirs. Our results illustrate that structurally improved BETis, such as UMB-136, may be useful as promising LRAs for HIV-1 eradication.